2013
DOI: 10.1155/2013/346581
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Possibilities of Nanosuspension

Abstract: Nowadays, a very large proportion of new drug candidates emerging from drug discovery programmes are water insoluble and thus poorly bioavailable. To avoid this problem, nanotechnology for drug delivery has gained much interest as a way to improve the solubility problems. Nano refers to particles size range of 1-1000 nm. The reduction of drug particles into the submicron range leads to a significant increase in the dissolution rate and therefore enhances bioavailability. Nanosuspensions are part of nanotechnol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 50 publications
(48 reference statements)
0
32
0
1
Order By: Relevance
“…183 The top-down method starts from large crystals to small NCs in a step-by-step manner during a high-energy process, such as pearl milling and high-pressure homogenization. 182,[184][185][186] The bottom-up method involves procedures that start from molecules to NCs, such as solvent exchange, 21,[187][188][189] high-gravity-control precipitation, 188,190,191 evaporative precipitation, 192 rapid expansion of supercritical solution, 193 and supercritical antisolvent methods. 194 DNCs prepared via bottom-up methods need less energy and are smaller compared with those prepared through top-down methods.…”
Section: Drug Nanocrystalsmentioning
confidence: 99%
“…183 The top-down method starts from large crystals to small NCs in a step-by-step manner during a high-energy process, such as pearl milling and high-pressure homogenization. 182,[184][185][186] The bottom-up method involves procedures that start from molecules to NCs, such as solvent exchange, 21,[187][188][189] high-gravity-control precipitation, 188,190,191 evaporative precipitation, 192 rapid expansion of supercritical solution, 193 and supercritical antisolvent methods. 194 DNCs prepared via bottom-up methods need less energy and are smaller compared with those prepared through top-down methods.…”
Section: Drug Nanocrystalsmentioning
confidence: 99%
“…3 Some other techniques that have illustrated reasonable successes involve enclosing the drug in vesicular nanoparticles (NPs) 5 or A nanosuspension is a submicron colloidal dispersion, approximately between 200 and 600 nm, of poorly watersoluble drug without any matrix that is stabilized by the presence of surfactants and/or polymers that prevent crystal growth or particles aggregation during storage. 9 Formulation of the drug in the form of nanosuspension enhances the absorption and bioavailability due to an increase in surface area and dissolution rate, which increases the rate and extent of absorption and hence the bioavailability. 9 Nanosuspension is more applicable for drugs that are characterized by high permeability and low solubility such as revaprazan.…”
Section: Introductionmentioning
confidence: 99%
“…9 Formulation of the drug in the form of nanosuspension enhances the absorption and bioavailability due to an increase in surface area and dissolution rate, which increases the rate and extent of absorption and hence the bioavailability. 9 Nanosuspension is more applicable for drugs that are characterized by high permeability and low solubility such as revaprazan. 10 Nanosuspension can be prepared either by the precipitation "bottom-up" or by the disintegration "top-down" technologies.…”
Section: Introductionmentioning
confidence: 99%
“…A research team, led by Guy G. Chabot, demonstrated that nano emulsion formulation of fisetin improves its bioavailability and antitumour activity in mice (49) . In recent years nanoemulsion has become a promising tool to improve bioavailability of several drugs along with nanosuspension and other various solubility enhancement techniques (61). Recent research on nanoemulsion preparation from various therapeutic classes has been summarized in Table 4 .…”
Section: Recent Trend In Nanoemulsionsmentioning
confidence: 99%